Crip Genealogies - Chen, Mel Y.; Kafer, Alison; Kim, Eunjung; Avril Minich, Julie (ANIMA: Critical Race Studies Otherwise, 2023)
The contributors to Crip Genealogies reorient the field of disability studies by centering the work of transnational feminism, queer of color critique, and trans scholarship and activism, showing how a white and Western-centric narrative of disability studies enables ableism and racism.